The Effect Of Naf Applıcatıon In Interdental Strıpped Enamel Surfaces On Perıodontal Tıssues - Neslihan Üçüncü; Mehmet Yalım (Galenos Yayinevi, 1990)
Interdental stripping is applied in cases where there are tooth size disharmonies in dental arches or in order to gain arch length. In the subjet procedure, it is not possible to eliminate the deep furrows which occur as a resuit of the use of diamond burrs or disk even the finest finishing strip is used. Thus, the predisposition for plaque retention is enhanced. In this study, the application of topical NaF and office-applied fluoride rinses in the stripped enamel surfaces has been investigated in order to evaluate the resulting effect for periodontal health and plaque accumulation. The plaque accumulation in the stripped surfaces has been observed and evaluated by the use of SEM.